إمكانية تطبيق حلقات الجودة وتأثيرها على جودة الخدمة في مؤسسة اتصالات الجزائر فرع سوق اهراس - محمد أمير مسلم; شيماء خراشي (My University, 2022)
This study aimed to show the correlation and influence between the service quality and quality circles. This study containd two parts, the first part deals with the theoretical aspect in whitch the study variable were dissected quality circle as an independent variable and service quality as a dependent variable, and the second part was devoted to the field study was carried out at Aalgeria telecom corporation unit Souk Ahras. Were the two reserchers mainly relied on distributing a questionnaire to a sample of 40 individuals, and 40 questionnaires were retrieved for statistical analysis with a response rate of 100 %. After the analysis process that relied on the SPSS statistical program, this study concluded: -There is a clear perception among the respondents about the quality and service quality cycles in the institution under study. -The study showed that there is a positive correlation between the quality cycles and service quality, and the most important relationship was between the implementation phase and service quality. -The study also showed that there is an impact relationship between quality circles and service quality, and the most important impact relationship was between the implementation phase and service quality. .................................................. هدفت هذه الدراسة إلى تبيان علاقة الارتباط والتأثير بين حلقات الجودة وجودة الخدمة .وقد احتوت هذه الدراسة على جزأين، الجزء الأول تناول الجانب النظري الذي تم فيه تشريح متغيرات الدراسة، حلقات الجودة كمتغير مستقل، وجودة الخدمة كمتغير تابع، أما الجزء الثاني فقد خصص للدراسة الميدانية التي تمت في مؤسسة اتصالات الجزائر وحدة سوق أهراس . حيث اعتمد الباحثان بشكل أساسي على توزيع استبانة على عينة مكونة من 40 فرد، وتم استرجاع 40 استمارة قابلة للتحليل الإحصائي بنسبة استجابة قدرت ب % 100.بعد عملية التحليل التي تم الاعتماد فيها على ال بنامج الإحصائي SPSS توصلت هذه الدراسة إلى:- هناك تصور واضح لدى المبحوثين عن حلقات الجودة وجودة الخدمة في المؤسسة قيد الدراسة.- أظهرت الدراسة أن هناك علاقة ارتباط موجبة بين حلقات الجودة وجودة الخدمة، وكانت أهم علاقة بين مرحلة التنفيذ وجودة الخدمة. - كما أظهرت الدراسة أن هناك علاقة تأثير بين حلقات الجودة وجودة الخدمة، وكانت أهم علاقة تأثير بين مرحلة التنفيذ وجودة الخدمة.